Knowledge and Practice on Menstrual Hygiene among Urban Adolescent Girls in Bangladesh - Haque, Md Jawadul; Karim, Md Rizwanul; Yasmin, Nelofar; Paul, Shubhra Prakash; Ara, Chaman; Parvin, Most Firoza; Ferdous, Rumana; Rahman, Md Asadur; nahar, Kowsarun; Arefin, Md Maruful (TAJ: Journal of Teachers Association, 2023)
Introduction: Menstruation-related poor knowledge and understanding among adolescent girls may lead to unsafe personal health care practice that ultimately increases the risk of genito-urinary tract infections, drop-out from school, poor academic performance, and overall poor quality of life. Being a developing country, it is an unrecognized problematic area in Bangladesh. Therefore, it is crucial to assess knowledge and practice on menstrual hygiene among urban adolescent girls in Bangladesh. Methods: This was a community-based cross-sectional study conducted in the Department of Community Medicine of Rajshahi Medical College among 495 purposively selected urban adolescent girls. Data were collected using a semi-structured interviewer-administered questionnaire. Results: The majority (57.2%) of the respondents in the study were more than 15 years old, and most (93.3%) were Muslim. Most of the girls (82.5%) have experienced menarche within the age range of 12-15 years, and the majority of respondents, 259 (52.32%), were informed about menstruation before menarche. Their source of information about menarche was mothers in most cases. Out of 495 adolescent girls who participated in this study, 70.9% had good knowledge of menstruation. About 82% of girls used commercially made sanitary pads, and 35.2% changed pads or clothes more than three times a day during menstruation. Conclusion: The majority (70.9%) of adolescent girls had good knowledge of menstruation, and 73.3% had a good practice on menstrual hygiene. Therefore, there is a need to design and implement universal awareness creation and advocacy programs to improve their knowledge of safe and healthy menstruation management and promote good hygienic practices by creating an appropriate supportive home and social environment for all the adolescent girls. TAJ 2022; 35: No-2: 01-11